2013
DOI: 10.1242/jcs.126714
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ receptor I transactivation mediates stretch-induced Pak1 activation and CTGF upregulation in mesangial cells

Abstract: SummaryIncreased intraglomerular pressure is an important pathogenic determinant of kidney fibrosis in the progression of chronic kidney disease, and can be modeled by exposing glomerular mesangial cells (MC) to mechanical stretch. MC produce extracellular matrix and profibrotic cytokines, including connective tissue growth factor (CTGF) when stretched. We show that p21-activated kinase 1 (Pak1) is activated by stretch in MC in culture and in vivo in a process marked by elevated intraglomerular pressures. Its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…17 Previous studies have demonstrated that Smad3 can be phosphorylated by transforming growth factor-β-independent pathways, such as JNK in lung epithelial cells, p38 in breast carcinoma cells, or directly by Pak1 in mesangial cells. [34][35][36] This is consistent with our data showing Pak1-dependent Smad3 phosphorylation through the MKK7-JNK signaling cascade. In addition, previous studies have reported that hypertrophy-induced microtubule network expansion can sequester Smad3, preventing it from being accessed and phosphorylated by the transforming growth factor-β receptor.…”
Section: Discussionsupporting
confidence: 92%
“…17 Previous studies have demonstrated that Smad3 can be phosphorylated by transforming growth factor-β-independent pathways, such as JNK in lung epithelial cells, p38 in breast carcinoma cells, or directly by Pak1 in mesangial cells. [34][35][36] This is consistent with our data showing Pak1-dependent Smad3 phosphorylation through the MKK7-JNK signaling cascade. In addition, previous studies have reported that hypertrophy-induced microtubule network expansion can sequester Smad3, preventing it from being accessed and phosphorylated by the transforming growth factor-β receptor.…”
Section: Discussionsupporting
confidence: 92%
“…TGFβ signalling is mediated by phosphorylation of SMADs, and by up-regulation of FOS, JUN and LXR transcription factors [ 28 , 34 , 36 , 55 , 60 , 61 ]. Consistent with this, we found that although the mRNA expression of SMADs 2 and 3 were not elevated in FCMs, levels of phosphorylated, nuclear localised SMAD2 were increased in granuloma FCMs relative to NFMs and in plaque FCMs, suggesting that TGFβ1 signalling was occurring.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic regulation was also observed in primary proximal cells whereas a prolonged inhibition of CTGF expression was detected in human distal tubular epithelial cells, reminiscent of the role for Rac1 in SRF activation described in MDCK cells [ 9 ]. Thus far, Rac1 inhibition has been related to CTGF expression primarily in mesenchymal cells such as fibroblasts [ 10 , 33 ], cardiomyocytes [ 34 ] or renal mesangial cells [ 35 ]. In all these studies, pharmacological or genetic inhibition of Rac1 correlated with reduced CTGF expression.…”
Section: Discussionmentioning
confidence: 99%